Chronic granulomatous disease and McLeod syndrome: Stem cell transplant and transfusion support in a 2-year-old patient—a case report - Helander, Louise; McKinney, Chris; Kelly, Kathleen; Mack, Samantha; Sanders, Mary; Gurley, Janice; Dumont, Larry J.; Annen, Kyle (Frontiers in Immunology, 2022)
Chronic granulomatous disease (CGD) with McLeod syndrome (MLS) is a contiguous gene deletion disorder characterized by defective phagocytic function and decreased Kell antigen expression. CGD cure is achieved through stem cell transplant (HSCT) usually in the peri-pubescent years. The presence of MLS makes peri-transfusion support complex however. Herein, we present the youngest known case of HSCT for CGD in the setting of MLS. A 2 year old male was diagnosed with CGD plus MLS. Due to the severity of the child’s systemic fungal infection at diagnosis, HSCT was deemed the best treatment option despite his small size and age. A related, matched donor was available and a unique red blood cell support plan had been implemented. Reduced intensity conditioning was used to reduce the transplant related mortality risk associated with myeloablative protocols. The transplant course was uneventful; autologous RBC transfusion support was successful and allowed for the avoidance of possible antibody formation if allogeneic units had been used. The patient achieved 1-year relapse free survival. The developed protocols provide a viable path to transplant in the very young and early transplant to cure could reduce disease related morbidity.